SLC6A20 transporter: a novel regulator of brain glycine homeostasis and NMDAR function - Mihyun Bae; Junyeop Daniel Roh; Youjoung Kim; Seong Soon Kim; Hye Min Han; Esther Yang; Hyojin Kang; Suho Lee; Jin Yong Kim; Ryeonghwa Kang; Hwajin Jung; Taesun Yoo; et al. (EMBO Molecular Medicine)
Abstract Glycine transporters (GlyT1 and GlyT2) that regulate levels of brain glycine, an inhibitory neurotransmitter with co‐agonist activity for NMDA receptors (NMDARs), have been considered to be important targets for the treatment of brain disorders with suppressed NMDAR function such as schizophrenia. However, it remains unclear whether other amino acid transporters expressed in the brain can also regulate brain glycine levels and NMDAR function. Here, we report that SLC6A20A, an amino acid transporter known to transport proline based on in vitro data but is understudied in the brain, regulates proline and glycine levels and NMDAR function in the mouse brain. SLC6A20A transcript and protein levels were abnormally increased in mice carrying a mutant PTEN protein lacking the C terminus through enhanced β‐catenin binding to the Slc6a20a gene. These mice displayed reduced extracellular levels of brain proline and glycine and decreased NMDAR currents. Elevating glycine levels back to normal ranges by antisense oligonucleotide‐induced SLC6A20 knockdown, or the competitive GlyT1 antagonist sarcosine, normalized NMDAR currents and repetitive climbing behavior observed in these mice. Conversely, mice lacking SLC6A20A displayed increased extracellular glycine levels and NMDAR currents. Lastly, both mouse and human SLC6A20 proteins mediated proline and glycine transports, and SLC6A20 proteins could be detected in human neurons. These results suggest that SLC6A20 regulates proline and glycine homeostasis in the brain and that SLC6A20 inhibition has therapeutic potential for brain disorders involving NMDAR hypofunction.